(untitled) (Al-Mansour Journal, 2022)
In this paper, face detection based on statistical method has been implemented to get accurately estimation to the crowd counting from an individual image. Random sample is used as statistical method to the estimation purpose. Once the image is given, Viola – Jones algorithm is implemented on the image and it give the number of faces on that image, then simple random sample is choose according to predefined condition which is the value of the last bounding rectangle box that surrounding the face on that image. The results show that proposed statistical method gives good result about (98%) by estimating the nearest true number of the crowd people than the standard face detection(Viola-Jones) technique when it used alone which give about 90% detection rate.